Strain Transformation Adjacent to the West Qinling Orogen: Implications for the Growth of the Northeastern Tibetan Plateau - Li, Zhangjun; Cheng, Feng; Hao, Ming; Young, Zachary M.; Song, Shangwu; Yang, Fan; Zhuang, Wenquan (Frontiers in Earth Science, 2021)
The West Qinling orogen has played an important role in accommodating the deformation in the northeastern Tibetan Plateau induced by the India-Eurasia convergence. Here we construct a vertical land motion (VLM) model based on the latest leveling observations adjacent to the West Qinling orogen. Combined with the horizontal deformation field, the crustal deformation pattern in this area is analyzed. Additionally, slip rate and coupling coefficients of the West Qinling fault, the longest fault separating the West Qinling orogen from the Lanzhou (Longxi) block, are inverted and constrained with GPS and VLM observations. Results show that the West Qinling fault slips slowly at a rate of 1–2 mm/yr and is strongly coupled with a moment magnitude deficit of Mw7.4. The crustal uplift rates adjacent to the West Qinling orogen are 0–3 mm/yr; which combined with 0–12.5ⅹ10−9/yr contraction rates, suggests that strain transformation plays a key role in controlling the tectonic uplift in the West Qinling orogen, and furthers our understanding of the contemporary geomorphic and topographic features. We identify a significant deformation transition belt at longitudes of 105°–106°E, which indicates that crustal deformation, induced from the northeastern expansion of the Tibetan Plateau, is mainly constrained to the plateau, rather than accommodated by crustal materials eastward escaping along the Qinling Mountains.